2020
DOI: 10.1039/d0nr05248e
|View full text |Cite
|
Sign up to set email alerts
|

Low loss waveguiding and slow light modes in coupled subwavelength silicon Mie resonators

Abstract: Subwavelength light-guiding optical devices have gained great attention in the photonics community because they provide unique opportunities for miniaturization and functionality of the optical interconnect technology. On the other hand,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 51 publications
2
13
0
Order By: Relevance
“…When a = 2.15 R , the metachain consisting of SDs with G = 0.5 R has the lowest α = 0.022 and that consisting of SDs with G = 0.9 R has the largest α = 0.507, which agree with the electric-field distributions in Figure a. The mechanism of long-range energy transfer in metachains is similar to previous studies based on magnetic mode coupling, whereas the different performances of metachains prove the vital value of the nonradiative resonant to transmission. Meanwhile, we notice that the SD with the G = 0.9 R metachain has higher efficiency when a is larger, indicating a limited tuning effect from the periodicity.…”
supporting
confidence: 86%
“…When a = 2.15 R , the metachain consisting of SDs with G = 0.5 R has the lowest α = 0.022 and that consisting of SDs with G = 0.9 R has the largest α = 0.507, which agree with the electric-field distributions in Figure a. The mechanism of long-range energy transfer in metachains is similar to previous studies based on magnetic mode coupling, whereas the different performances of metachains prove the vital value of the nonradiative resonant to transmission. Meanwhile, we notice that the SD with the G = 0.9 R metachain has higher efficiency when a is larger, indicating a limited tuning effect from the periodicity.…”
supporting
confidence: 86%
“…An experimental study of metal particle arrays revealed the effects of collective lattice resonances which provide laser generation 17 , 18 , biosensing applications 19 , 20 and amplification of light radiation 21 23 . In addition to creating antireflection coatings, arrays of ordered dielectric particles can be used in optical waveguides 24 , 25 and also as metasurfaces and metamaterials 23 , 26 . Particular attention is paid to the study of the interaction of resonant modes, excited in individual dielectric particles, with lattice modes.…”
Section: Introductionmentioning
confidence: 99%
“…This is the first time that such an extended array of coupled resonators comprising up to 18,000 coupled Mie-resonant NPs is reported, with the measured loss value unprecedented for resonant arrays and comparable to conventional SWG waveguides 13 . While earlier work 46 reported slightly lower losses, note that the silicon NP chains investigated in there operate in the subwavelength regime below the bandgap thus are fundamentally SWG waveguides 14 , unlike our NP chains operating above the bandgap. (where c is the speed of the light in the vacuum, ng is the group index, and L is the geometrical path difference between the MZI arms).…”
Section: Experimental Demonstrationmentioning
confidence: 51%